Creativity of Kazakh people in the context of kara jorga dance: preservation and development prospects of Kazakh cultural heritage - Saitova, Gulnara; Jumasseitova, Gulnara; Kulbekova, Aigul; Moldakhmetova, Alima; Izim, Toigan (Creativity Studies, 2023)
This research is devoted to the study of the examples of the early Kazakh folk dance kara jorga, also referred to as the dance of joints, preserved on the territory of Kazakhstan, China, Mongolia, and the Altai Region (Western Siberia, Russia). Research based on a generalized art history analysis, the characteristics of the performance of Kazakh dances on the territory of China, Mongolia, the Altai Region, and Kazakhstan are presented. The results of the study were obtained with the help of the historical analysis of the traditional culture of the Kazakhs of the 20th and the beginning of the 21st centuries, search expeditions, the study of scientific and methodological methods of professional and creative skills of performers, as well as the performing, research, and pedagogical experience that we have accumulated. Research includes analysis dance kara jorga in the aspect of “first” and “second” existence. It is considered in the context of two components of creativity (first – novelty, second – usefullness, effectiveness, or value) and the prospects of its application in the field of dance therapy.